Kauneuden kirous - Riehl, Wilhelm Heinrich, 1823-1897; Jalava, Antti, 1846-1909 (Salt Lake City, UT : Project Gutenberg, 2008)
"Kauneuden kirous" by Wilhelm Heinrich Riehl is a novel written in the late 19th century. The narrative begins with the birth of a remarkably beautiful boy named Amos, the son of a tailor, who is destined for greatness and admiration but is also burdened by the societal expectations that his beauty incurs. As Amos grows, the story explores the complexities of beauty, envy, and the accompanying hardships, setting the stage for a deeper exploration of his character and fate. At the start of the novel, the extraordinary beauty of young Amos immediately captivates everyone around him, prompting concerns about the fate that such beauty might bring. The townspeople are enchanted, but this admiration soon turns to envy and mockery, especially among his peers, leading to a troubled childhood marked by both admiration and scorn. As Amos matures, he grapples with his identity, the expectations placed upon him due to his looks, and the unfortunate prospects that accompany such beauty in a turbulent world filled with war and strife. The opening sets a tone for a serious reflection on the burdens of physical beauty and how it shapes life s journey, suggesting that it may indeed be more of a curse than a gift. (This is an automatically generated summary.)
Release date is 2008-11-17
Produced by Tapio Riikonen
Keywords: German fiction -- Translations into Finnish